PEMBINAAN KEMAHIRAN BERBAHASA INGGRIS PROFESI DAN LITERASI HUKUM KOMUNIKASI BAGI GURU DAN SISWA DI MTS MANBAA’UL NURUL HIDAYAH BATAM - Afriana Afriana; Tomi Arianto; Padrisan Jamba (PUAN INDONESIA, 2022)
The ability to speak English is one of the skills that must be possessed by students as their expertise that can be used in the field of work and is also important for teachers to teach and practice in the learning process. In the world of work, children who have graduated are required to have skills in communicating in English, and communication students are also expected to understand communication literacy. Many are good at speaking English but sometimes lack direction and lack of knowledge about communication literacy. On this occasion, the lecturers of Putera Batam University held a Coaching for Students and Teachers on Profession English Proficiency and Communication Law Literacy for Teachers and Students at MTs Manbaa'ul Nurul Hidayah Batam. The method used is by collecting data from observations, questionnaires and group discussions. The result of this service is that participants already understand English and communication legal literacy. There are 60% of the participants who have practiced English and communication law literacy.